Social variables and the role of vocational training in achieving the requirements of the labor market in Iraq: A field sociological research in Al-Diwaniyah city - Alawe Abdullah, Hussain (International Journal of Psychosocial Rehabilitation, 2020)
The economic policies of some countries have played a large role in showing many problems which are related to the labor market, as a result of taking ill-considered policies and following them without achieving the desired goal, such as economic openness and what the wrong policies does include, such as reducing the number of jobs in the government sector by stopping appointments or layoffs of some workers and lower wages. These policies have an impact on the Iraqi labor market, that the importance of current research is by addressing these policies of social and economic changes which are affecting the requirements of the labor market, as what are the problems caused by these factors, as the research aims to identify the social characteristics of the groups which are most interested in vocational training centers, highlighting the role of education, training of professionals and technicians in requiring the job market in Iraq. The researcher has used the social survey method in the sample, as the research community represented the trainees in the vocational training department in Diwaniya, while the study was applied to a random sample of (117) singles. The results of the research showed that the number of males exceeds the number of females because the professional specialties are the prerogative of the males, because their nature does not suit females, as we find that the majority of the sample members see a contribution that qualifies training programs to create real job opportunities more abundant and continuity for those looking for it, as it was clear from the majority of the respondents that they see that the contribution of vocational training programs for creating a solution to the unemployment problem, this is through its ability to provide real and quick job opportunities for the beneficiaries, at last, the results of the field research showed that the technical skills that graduates had received in their specializations are qualifying them to do their job to the fullest with the best way.